Hubungan Riwayat Anemia Ibu Saat Hamil Dengan Kejadian Stunting Pada Balita Di UPTD Puskesmas Batui Kabupaten Banggai - Ely Kurniati; Yusda Seman MY; Warlinda (Window of Public Health Journal, 2025)
Anemia, particularly iron deficiency anemia, is a condition in which the body does not have enough healthy red blood cells to carry oxygen to the body's tissues. In pregnant women, anemia can impact fetal health, including the risk of premature birth, low birth weight, and stunting. Children who experience stunting tend to have stunted growth and less than optimal cognitive development. To determine and analyze the relationship between maternal anemia history during pregnancy and the incidence of stunting in toddlers at the Batui Community Health Center (UPTD), Banggai Regency. This study used an analytical survey with a cross-sectional study approach. The population in this study was 224 mothers with toddlers. The total sample was 69 people. This study used a questionnaire. The data analysis test used the chi-square test. This study's conclusion shows that most mothers at the Batui Community Health Center (UPTD), Banggai Regency, did not experience anemia during pregnancy, and most toddlers did not experience stunting. However, there was a significant relationship between maternal anemia history during pregnancy and the incidence of stunting in toddlers. The Chi-Square test produced a p-value of 0.000, confirming that anemia in pregnant women is closely related to toddler stunting.